2009
DOI: 10.1353/dem.0.0050
|View full text |Cite
|
Sign up to set email alerts
|

Job loss and health in the U.S. labor market

Abstract: While U.S. unemployment rates remain low, rates of job loss are high and rising. Job loss is also becoming increasingly common in more advantaged, white-collar occupations. This article is concerned with how these patterns impact the health of U.S. workers. Drawing on recent data from the U.S. Panel Study of Income Dynamics, I find that job loss harms health, beyond sicker people being more likely to lose their jobs. Respondents who lost jobs but were reemployed at the survey faced an increased risk of develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(113 citation statements)
references
References 37 publications
2
100
1
4
Order By: Relevance
“…Job loss has been linked to both short and long-term declines in physical health, including worse self-reported health, physical disability, cardiovascular disease, a greater number of reported medical conditions, increase in hospitalization, higher use of medical services, higher use of disability benefits, an increase in self-destructive behaviors and suicide, and mortality (Burgard, Brand, and House 2007; Catalano et al 2011; Dooley, Fielding, and Levi 1996; Ferrie et al 1998; Gallo et al 2000; Gallo et al 2004; Gallo et al 2006b; Gallo et al 2009; Kasl and Jones 2000; Kessler, Turner, and House 1988; McKee-Ryan et al 2005; Strully 2009; Turner 1995). For example, Gallo et al (2004, 2006b) found that job loss doubled the risk of subsequent myocardial infarction and stroke among older workers.…”
Section: Non-economic Effects Of Job Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Job loss has been linked to both short and long-term declines in physical health, including worse self-reported health, physical disability, cardiovascular disease, a greater number of reported medical conditions, increase in hospitalization, higher use of medical services, higher use of disability benefits, an increase in self-destructive behaviors and suicide, and mortality (Burgard, Brand, and House 2007; Catalano et al 2011; Dooley, Fielding, and Levi 1996; Ferrie et al 1998; Gallo et al 2000; Gallo et al 2004; Gallo et al 2006b; Gallo et al 2009; Kasl and Jones 2000; Kessler, Turner, and House 1988; McKee-Ryan et al 2005; Strully 2009; Turner 1995). For example, Gallo et al (2004, 2006b) found that job loss doubled the risk of subsequent myocardial infarction and stroke among older workers.…”
Section: Non-economic Effects Of Job Lossmentioning
confidence: 99%
“…Effects of job losses for non-health reasons on self-rated poor health are relatively small (Burgard, Brand, and House 2007). Studies of plant closures also show that workers’ health declines following job loss (Arnetz et al 1991; Beal and Nethercott 1987; Gore 1978; Iversen, Sabroe, and Damsgaard 1989; Kasl and Cobb 1970; Kessler, House, and Turner 1987; Strully 2009). …”
Section: Non-economic Effects Of Job Lossmentioning
confidence: 99%
“…In general, involuntary routes, most notably unemployment, have adverse effects on mental and physical health, such as depression and anxiety (5), hypertension, arthritis or diabetes (6,7), and may lead to higher mortality (8,9) among unemployed persons (10,11). While contradictory findings have been reported for voluntary routes.…”
mentioning
confidence: 99%
“…Mathers, Schofi eld 1998]. Strully [2009] zjistila, že špatný zdravotní stav zvyšuje pravděpodobnost ztráty zaměstnání, a to jak jeho dobrovolného opuštění, tak riziko výpovědi. Zdravotní stav je nutnou kontrolní proměnnou, a to zejména při analýze, která se (podobně jako naše) zaměřuje na star-ší osoby.…”
Section: Struktura Nezaměstnanostiunclassified